Approach of Happiness and Employee Engagement in Happy Workplace Organization Model - แก้วเกิด, วิริยาภรณ์; แสดงหาญ, พรรัตน์; อิงอาจ, อภิญญา (KKBS Journal of Business Administration and Accountancy, 2017)
This research aimed at identifying the operational approach for a happy workplace organization and happiness creation, as well as happiness in work and employees engagement. It also looked at the approaches for happiness creation which yielded an impact on the employee engagement to the organization, of which the happiness in work could be transferred from the happy workplace organization model. Mix-method and exploratory sequential were adopted for this research through an adoption of case study strategies. The findings revealed that, in regard to the operational approach in a happy workplace organization model, there were happy 8 menu of activity arrangements in accordance with the happiness creation approach listed as follows: happy body, happy heart, happy relax, happy brain, happy soul, happy money, happy family, and happy society. Regarding the activity arrangement, there must be a design corresponding to the employees’ life quality. Besides, as a whole, the employees agreed, rated at the ‘rather high’ level, with the happiness creation approach, happiness in work, and their engagement to the organization. For the happiness creation approach according to the happy 8 menu items of activity arrangementsarranged for the employees by the organization, it yielded the impact on the employees’ happiness in work. Likewise, their happiness in work also yielded the impact on their organization engagement. In conclusion, the mentioned happy 8 menu of the happiness creation approach activities arranged for the employees by the organization gave an effect on the employee engagement to their organization